2009
DOI: 10.1111/j.1468-0432.2009.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender in Varying Forms of Flexible Working

Abstract: In this article we present empirical data from a research study investigating the implementation of the flexible working policies that emanate from the improving working lives standard in a National Health Service Trust in the UK. We argue that gender is accorded insufficient focus in the literature, considering the barriers that create a take-up gap in formal flexible working practices. We further argue that gendered perceptions render unworkable attempts to portray flexible working as a gender-neutral issue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 18 publications
(51 reference statements)
2
87
1
2
Order By: Relevance
“…Although previous studies have found that women are less likely to have access to flexible working time options than men are (e.g. Golden, 2001Golden, , 2008Atkinson and Hall, 2009), they take those options up more than men do (Giannikis and Mikhail, 2011;Kossek et al, 1999). The decision to use the option of flexible working time is mainly driven by family responsibilities, which could explain these findings (Albion, 2004;Sarbu, 2014).…”
Section: Literature Reviewcontrasting
confidence: 40%
“…Although previous studies have found that women are less likely to have access to flexible working time options than men are (e.g. Golden, 2001Golden, , 2008Atkinson and Hall, 2009), they take those options up more than men do (Giannikis and Mikhail, 2011;Kossek et al, 1999). The decision to use the option of flexible working time is mainly driven by family responsibilities, which could explain these findings (Albion, 2004;Sarbu, 2014).…”
Section: Literature Reviewcontrasting
confidence: 40%
“…The BHPS/Understanding Society lacks employer-reported data on availability/use of FWAs which would enable assessment of gaps in knowledge pertaining to FWA availability. Meanwhile, research should also explore the relative incidence and impact of informal flexibility, shown to offer employees greater control over the distribution of work-time (Hall and Atkinson, 2006;Atkinson and Hall, 2009). It will also be important for future research to consider the effects of the recent extension of 'right to request' in the FWRs.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the overencompassing challenge of women having to maintain a peculiar balance between their ever-conflicting roles, as childbearer and as full-time employee (Atkinson & Hall, 2009). Empirical evidence indicates that, even within DCC households, gender disparities in decision making and time allocation still remains an incitement, with some degree of disagreement and compromise extremely persistent (Wheatly, 2013).…”
Section: Attainments and Challenges In Paternity Leavementioning
confidence: 99%